Theraupetic sebagai Konsep Desain Fasilitas untuk Lansia Dimensia di Sidoarjo, Jawa Timur - Yanuar, Dimas Audri; Laksono, Sigit Hadi (Institut Teknologi Adhi Tama Surabaya, 2020)
Abstract. Elderly (elderly) is someone who is categorized in an age that reaches the age of 60 years or more. With age the physical ability and motor ability of a person also decreases. Reporting from the data of the demographic affairs office of Sidoarjo district in November 2019, the number of elderly population reached 270,881 inhabitants. With increasing age, the level of memory in the brain decreases which result in senility (dementia). Generally, the elderly are placed in a nursing home where their daily activities are limited so that elderly people in nursing home experienced stress and cause dementia to get worse. Dementia is considered prevalent in most communities, so the people with dementia are not early detected. Dementia is divided into 4 types, namely: Alzheimer, Lewy Body, Vascular and Parkinson. Each type of dementia has different treatment so the therapy process can run effectively. In the process of planning and designing a therapeutic complex for elderly people with dementia in the Sidoarjo District are applying the rules of behavior architectural themes in which each dementia complex has different facilities and it's assessed based on the user. Also, helping government programs written in the Sidoarjo district regional regulation number 4 of 2010 regarding Elderly Welfare, The government is obliged to provide services and social protection for the elderly so that they can actualize and enjoy a decent standard of living.Keywoards : Theraupetic, Elderly, DementiaÂ Abstrak.Â Lansia (lanjut usia) adalah seseorang yang dikategorikan dalam usia yang mencapai usia 60 tahun atau lebih. Dengan seiring bertambahnya usia, kemampuan fisik dan kemampuan motorik seseorang juga menurun. Dilansir dari data dispenduk kabupaten sidoarjo November 2019, jumlah penduduk lansia mencapai 270.881 jiwa. Dengan bertambahnya usia, tingkat memori dalam otak akan semakin menurun yang mengakibatkan kepikunan (demensia). Umumnya, lansia ditempatkan pada sebuah panti jompo yang mana kegiatan sehari-harinya dibatasi sehingga banyak lansia yang berada di dalam panti jompo mengalami stress dan menyebabkan penyakit demensia semakin memburuk. Kepikunan dianggap hal lazim pada sebagian besar masyarakat, sehingga penderita demensia tidak terdeteksi sejak dini. Demensia dibagi menjadi 4 jenis, yaitu : Alzheimer, Lewy Body, Vaskuler dan Parkinson. Setiap jenis demensia memiliki penanganan yang berbeda agar proses terapi bisa berjalan dengan efektif. Pada proses perencanaan dan perancangan kompleks therapeutic untuk lansia demensia di kabupaten sidoarjo menerapkan kaidah-kaidah tema arsitektur perilaku dimana pada setiap kompleks demensia memiliki fasilitas yang berbeda dan dikaji berdasarkan pengguna. Serta, membantu program pemerintah yang tertulis berdasarkan peraturan daerah kabupaten Sidoarjo Nomor 4 Tahun 2010 tentang Kesejahteraan Lanjut Usia, pemerintah berkewajiban memberikan pelayanan dan perlindungan sosial bagi lansia agar mereka dapat mewujudkan dan menikmati taraf hidup yang layak.Kata Kunci : Theraupetic, Lansia, Demensia